14 Next generation sequencing (NGS) approach to identify genetic alterations in head and neck squamous cell carcinoma. Issue 5 (May 2015) - Niehr, F.; Konschak, R.; Liebs, S.; Munz, M.; Budach, V.; Keilholz, U.; Tinhofer, I.
Abstract : Introduction: Next-generation sequencing (NGS) techniques render genetic investigations of tumor material more effective and will help to understand tumor biology and overcome mechanisms of treatment resistance. Targeted NGS which is feasible also for archival FFPE tumor material represents an attractive approach for the development of personalized cancer treatment. We describe here the establishment of an HNSCC-specific cancer gene panel for targeted NGS. Methods: NGS data available at the cBioPortal reporting on whole exome sequencing of 412 HNSCC samples from three independent patient cohorts (Broad Institute, Science 2011; John Hopkins University, Science 2011; TCGA, provisional) were used. For the definition of relevant genes to be included in a specific HNSCC gene panel, selection criteria such as the relative mutational frequency in HNSCC, the presence of hotspot mutations within the coding region or the occurrence of mutations at recurrent positions were used. In order to consider the biological function of particular genes, genes were mapped to pathways using different databases. Results: Overall, 1710 genes with genetic alterations fulfilling the selection criteria were identified in the HNSCC datasets. Of these, less than 10% of affected genes were altered in more than 5% of patients, speaking for a huge genetic heterogeneity of head and neck cancer. By our selection criteria, a gene set of 901 genes was identified, covering a coding region of 2.94 Mb in total. Of these genes, only 652 could be mapped to specific pathways, resulting in a final coding region length of the selected genes of 2.15 Mb to be targeted by panel NGS. The gene list covered a wide spectrum of already known but also novel unexpected genetic lesions. Conclusion: Application of NGS for comprehensive molecular characterization of HNSCC revealed new insights into HNSCC biology and is expected to lead to the identification of new druggable targets also for this tumor entity. The gene list obtained by our approach can be used for the establishment of an HNSCC-specific panel for targeted NGS. Such a gene panel will help in the assessment the intratumor genetic heterogeneity and the characterization of spontaneous and treatment-induced clonal evolution of tumors and will thereby contribute to the development of personalized medicine in HNSCC.